Assaying the effect of VEGFR2 receptor inhibition on preimplantation mouse embryo development - Holzer, Michael (Jihočeská univerzita, 2019)
The aim of this thesis was to investigate the potential role of the Vascular endothelial growth factor receptor 2 (VEGFR2) in the cell fate decision in mouse preimplantation development.
Assaying the effect of VEGFR2 receptor inhibition on preimplantation mouse embryo development.